2013
DOI: 10.5539/ibr.v6n9p54
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy for Customer Engagement: How Do French Firms Use Social CRM?

Abstract: A company is no longer only focused on winning market share or increasing demand, but also on customer relationships, engagement and retention. The idea of improving relationships with customers by using social media is called social customer relationship management (SCRM). The objective of this exploratory research is to define a grid of analysis of a SCRM strategy. To do so, a double analysis was conducted: a qualitative research on CAC 40 French firms and a quantitative survey on customer's perception of SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
2
28
0
4
Order By: Relevance
“…Since SCRM implementation entails processes related to IT and marketing functions (Huang and Wang, 2013;Olszak and Bartus, 2013;Payne and Frow, 2005), the questionnaire was sent to the Chief Executive Officers or senior managers whose main responsibility at their firm was either IT management, marketing management or both types of management combined. As no data on SCRM activities for the targeted sample population in Australia is publicly available, a survey questionnaire was developed based on the extant literature (Acker et al, 2011;Baird and Parasnis, 2011;Cappuccio et al, 2012;Dutot, 2013;Greenberg, 2009;Leary, 2008;Stone, 2009). The questionnaire was also pretested in discussion with several SME owner-managers as well as with senior academic researchers in the fields of IT and marketing to ensure clarity and content validity.…”
Section: Methodsmentioning
confidence: 99%
“…Since SCRM implementation entails processes related to IT and marketing functions (Huang and Wang, 2013;Olszak and Bartus, 2013;Payne and Frow, 2005), the questionnaire was sent to the Chief Executive Officers or senior managers whose main responsibility at their firm was either IT management, marketing management or both types of management combined. As no data on SCRM activities for the targeted sample population in Australia is publicly available, a survey questionnaire was developed based on the extant literature (Acker et al, 2011;Baird and Parasnis, 2011;Cappuccio et al, 2012;Dutot, 2013;Greenberg, 2009;Leary, 2008;Stone, 2009). The questionnaire was also pretested in discussion with several SME owner-managers as well as with senior academic researchers in the fields of IT and marketing to ensure clarity and content validity.…”
Section: Methodsmentioning
confidence: 99%
“…Customers now even expect companies to be present in OSN and use them as a communication platform, such that they become almost inevitable for improving customer relationships and brand perceptions (Dutot, 2013). To do so, companies increasingly launch corporate profile pages (so-called 'fan pages'; Kim et al, 2010;Wen, Tan, & Chang, 2009), and create marketer-generated content with the goal of simultaneously promoting their brands and advertising specific products or services (Scholz et al, 2013).…”
Section: Research Background: Ewom In the Purchase Decision Process Amentioning
confidence: 99%
“…That dialog, between the company and the customers, leads to a collaborative experience . The main goal of SCRM is achieving customer engagement by transforming relationships from a perception of being a customer to one of being a partner …”
Section: Theorymentioning
confidence: 99%
“…Research on SCRM is devised mainly through one of two approaches: the first is theoretical and the second is empirical based on surveys. Dutot tested the SCRM implementation of CAC‐40 French firms through a quantitative customer survey. He found that customers follow brands to remain aware of their activity but not necessarily to communicate with them.…”
Section: Theorymentioning
confidence: 99%